THE ORGANIZATIONAL CULTURAL ROLE IN IMPROVING EMPLOYEE PERFORMANCE - Yuliana Yuliana (Yayasan Education and Social Center, 2022)
A solid organizational culture flexible enough to adapt to shifting conditions in the business world requires successfully running a company in today's highly competitive environment. For an excellent corporate culture, there need to be leaders who can create a culture for their teams that can compete successfully in the business world. The ability of leaders to carry out the vision and mission of the company at the beginning is essential because it will determine the company's ability to compete in the global business world. Therefore, leaders must be able to carry out the company's vision and mission established at the beginning. The research strategy employed is a descriptive approach, a subset of qualitative research strategies. Qualitative researchers using a descriptive methodology collect their data primarily through in-depth interviews and written records. Through interviews and documentation, we collect data that analyzing by selecting relevant information, sorting it, and drawing conclusions based on our best-educated guesses. An organization's culture can motivate workers to do better, which in turn helps the company reach its goals. When an employee's actions allow the company to get past a challenge, that's when the culture has succeeded. It turns out that a company's culture affects employees' productivity in both obvious and subtle ways. It's even arguable that a company's culture significantly impacts how its workers perform